Konseling Individu Teknik Self Talk Untuk Meningkatkan Kepercayaan Diri Siswa - fira, Musfira (Jurnal Pendidikan Dasar dan Menengah (Dikdasmen), 2025)
In actualizing the potential possessed by students, self-confidence is an important aspect. Apart from that, low self-confidence is also a problem that hinders student development. Individual counseling is one of the efforts of guidance counselors or school counselors to increase students' self-confidence. This research uses a qualitative approach to the clinical case study type with data collection techniques through interviews, observation and documentation. The data obtained was analyzed using qualitative descriptive analysis. To overcome the problems experienced by the subject, the self-talk technique was given. Based on the assistance given to the subject, the results obtained were that the subject experienced many changes, especially in socializing, such as being good at communicating and showing active and positive behavior. However, he has not been able to explore his abilities.